The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/21645515.2019.1572410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal antibody on the infant immune response to inactivated poliovirus vaccines made from Sabin strains

Abstract: This study aimed to evaluate the effect of maternally derived antibody on the immunogenicity of Sabin IPV. A total of 600 infants were randomized to receive one of the five different vaccines: the high-(group A), medium-(group B) or low-dose (group C) of investigational Sabin IPV, the control Salk IPV (group D) or the control Sabin IPV (group E), at 2, 3 and 4 months of age. The post-vaccination GMTs, GMIs and seroconversion rates of poliovirus type-specific neutralizing antibody were analyzed for different ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(26 reference statements)
1
8
1
Order By: Relevance
“…This may indicate that candidate sIPV type-3 is sufficiently immunogenic to overcome interference with maternal antibodies, but it was notable that type-3 seropositivity due to maternal Abs was generally lower compared with types-1 and −2. This was most evident using Sabin viruses in the assay, and reflects the same observation made in the Puerto Rican study [28] for Salk vaccine and more recently by Tang et al [30] who also found that Sabin types 1 and 2 were most sensitive to this apparent interference, and the lower type-2 responses to a single dose of IPV at 16 weeks of age in seropositive infants [29] . The mothers of these infants would have been immunized with Sabin OPV, which was the standard of care in Panama until 2014 when the three infant primary doses were replaced by IPV.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This may indicate that candidate sIPV type-3 is sufficiently immunogenic to overcome interference with maternal antibodies, but it was notable that type-3 seropositivity due to maternal Abs was generally lower compared with types-1 and −2. This was most evident using Sabin viruses in the assay, and reflects the same observation made in the Puerto Rican study [28] for Salk vaccine and more recently by Tang et al [30] who also found that Sabin types 1 and 2 were most sensitive to this apparent interference, and the lower type-2 responses to a single dose of IPV at 16 weeks of age in seropositive infants [29] . The mothers of these infants would have been immunized with Sabin OPV, which was the standard of care in Panama until 2014 when the three infant primary doses were replaced by IPV.…”
Section: Discussionsupporting
confidence: 79%
“…Other recent studies in Panama found a similar profile of prevaccination seropositivity rates (47.6–52.2%, 51.9–62.6% and 20.6–24.2% for Salk virus types-1, -2 and -3, respectively) [22] and 60.7% for Salk type-2 only [23] , due to maternal antibodies in 6 week-old infants. Interference by maternal antibodies with the responses to IPV has been established, [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , and acknowledged by the WHO, the SAGE recommending that when a single dose of IPV is given in the mixed bOPV and IPV series it should be administered at 14 weeks of age [32] . A Puerto Rican study directly compared responses to Salk IPV administered in either the 6,10,14 weeks or 2,4,6 months schedules and found responses to types-1 and -2 were significantly lower with the earlier schedule [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The finding was consistent with our previous phase III study [21], but these values are slightly lower than those of another double-blinded phase III clinical trial conducted in 2012-2014 [22], which may be due to the relatively high level of maternal antibodies in our study. Previous studies have shown that high levels of maternal poliovirus antibodies could attenuate the antibody responses to the IPVs [23][24][25]. Of note, in the present study, the post-vaccination GMTs of poliovirus types 1, 2 and 3 in the investigational sIPV group were noticeably higher than those in the IPV group.…”
Section: Discussioncontrasting
confidence: 51%
“…Several lines of evidence suggest that maternal antibodies transferred via the placenta can limit vaccine responses in infants by capturing vaccine antigens, thereby neutralizing the induction of a de novo immune response as is proposed to occur for the tetanus, poliovirus, and measles vaccines (Osterhaus et al, 1998;Jones et al, 2014;Tang et al, 2019). Mechanistically, it is proposed that maternally derived antibodies specifically opsonize vaccine antigens, driving enhanced clearance via the inhibitory receptor, FcgRIIB, resulting in an overall dampened immune response (Karlsson et al, 2001).…”
Section: Maternal Bm Antibodies On Neonatal Vaccine Responsesmentioning
confidence: 99%